Effect of Laser Shock Peening without Coating on Grain Size and Residual Stress Distribution in a Microalloyed Steel Grade - Calvin Samuel; Arivarasu MOGANRAJ; Sathya Swaroop; K. Praveenkumar; Arivazhagan Natarajan; Muktinutalapati Nageshwara Rao; Badirujjaman Syed; Basudev Bhattacharya (Crystals, 2023)
This study aimed to identify the optimal combination of wavelength and laser pulse density to achieve the optimal pulse pressure that can induce the maximum compressive residual stress at the subsurface of microalloyed steel. For this, laser shock peening without coating (LSPwC) was performed on microalloyed steel samples at the fundamental wavelength (1064 nm) with pulse densities of 3, 6, 9, and 12 GW/cm2 and at the second harmonic wavelength (532 nm) with pulse densities of 3, 6, and 9 GW/cm2. The residual stress distributions were studied to a depth of 500 µm in the laser-treated samples. Tensile residual stress was observed at the surface of laser-peened specimens in both wavelength conditions (1064 and 532 nm). The significant impartment of compressive residual stress across the depth was achieved at the fundamental wavelength (1064 nm). The maximum compressive residual stress was attained with a laser pulse density of 9 GW/cm2 in the 1064nm wavelength condition. The optical micrographic analysis in the subsurface regions of the LSPwC specimen at 1064 nm and 9 GW/cm2 shows evidence of a high degree of plastic deformation. Electron backscatter diffraction (EBSD) analysis shows that there is grain refinement due to plastic deformations in samples subjected to the fundamental wavelength. Microhardness distribution analysis across the subsurface region shows work-hardening effects in the laser-processed samples in the 1064 nm condition. This study also shows that there is an indication of a thermal softening effect in the samples treated with the 532 nm wavelength, and it is correlated with lower compressive residual stress across the depth.